Design and Fabrication the Control Mechanism to Improve the Wave Energy Converter’s Efficiency - Phan Công Bình; Nguyễn Nhựt Phi Long; Hồ Xuân Thành; Đỗ Tiến Sĩ (Journal of Technical Education Science, 2024)
This article presents a design and fabrication of a control mechanism of a wave energy converter (WEC). Survival level and the overall efficiency of the WEC are significant factors in the wave energy harvesting field. Trying to face these challenges, an innovative conceptual design is proposed to minimize the influence of work environment and possibly to improve performance of the WEC. First, a device structure is presented to describe the working mechanism. Based on the geometric parameters of the floating buoy, hydrodynamic parameters are obtained in the frequency domain by using the wave interaction software ANSYS AQWA. Then, the time domain simulation program is performed by the use of MATLAB/Simulink software. Next, the test rig is fabricated and installed in the wave maker. Finally, experimental results under different wave conditions are carried and compared with that of the analytical model. These results show that the analytical model is in good agreement with experimental results. Moreover, the overall efficiency is significantly improved by adjusting the position of the center of mass.